Differential Diagnosis Between Venomous (Bothrops jararaca, Serpentes, Viperidae) and “Nonvenomous” (Philodryas olfersii, Serpentes, Dipsadidae) Snakebites: Is It Always Possible? - de Medeiros, Carlos R.; Duarte, Marcelo R.; de Souza, Solange N. (Wilderness & environmental medicine, 2021)
Bites of “nonvenomous” snakes can sometimes be mistaken for the bites of venomous snakes. As an example of this confusion, this report describes confirmed bites by Philodryas olfersii and Bothrops jararaca. In the first case, a 55-y-old man with a history of controlled hypertension was bitten on his right forearm by P olfersii. Physical examination revealed extensive edema, erythema, and widespread ecchymoses throughout his right upper limb. Laboratory tests indicated leukocytosis and high D-dimer levels, but normal coagulation, suggestive of a resolved recent coagulopathy. He received only supportive treatment. In the second case, a healthy 35-y-old man was bitten by B jararaca. Although the anatomic region of the bite and the results of physical examination were similar to those in the first case, laboratory tests showed mild coagulopathy, leukocytosis, and high D-dimer levels. The patient was treated with antivenom. In both cases, the 20-min whole blood clotting test results were normal. Patients bitten by P olfersii may present with local symptoms resembling B jararaca envenomation. Without snake identification and the detection of venom-induced consumption coagulopathy, especially in places where the 20-min whole blood clotting test is the only clotting test available, it is almost impossible to establish an accurate and safe differential diagnosis. In this context, the best alternative is to take the risk of prescribing antivenom for a possible P olfersii bite rather than failing to do so for a real Bothrops bite. Late treatment for Bothrops bite can result in severe complications and sequelae.